Poetic rhythm : structure and performance : an empirical study in cognitive poetics - Tsur, Reuven, 1932-2021 (Brighton [England] ; Portland [OR] : Sussex Academic Press, 2021)
This research is an instrumental investigation of a theory of rhythmical performance of poetry, originally propounded speculatively in the author's Perception-Oriented Theory of Metre (1977). "Iambic pentameter" means that there is a verse unit consisting of an unstressed and a stressed syllable (in this order), and that the verse line consists of five such units. In the first 165 verse lines of Paradise Lost there are two such lines. The theory takes up one of the central issues in metrical studies: all criteria for metricality hitherto proposed have been violated by the greatest masters of musicality in English poetry. The question arises, how do we recognise two verse lines that are very different in their structures as instances of the same abstract pattern of, eg: iambic pentameter; and how do we distinguish a metrical from an unmetrical line. One great difference between this theory of metre and others concerns the status of deviation. Most theoreticians deploy a battery of tools to make deviant stress patterns conform with metric pattern. Only when all attempts fail do they speak of "tension". When they succeed, they blur the distinction between, for example, Milton's and Pope's metrical styles. Or else, they have formulated different rules of metricality for Shakespeare and Milton. This theory assumes that when the versification patterns and linguistic patterns conflict, they can be accommodated in a pattern of "Rhythmical Performance" -- namely one in which the conflicting patterns are simultaneously perceptible. There are scales of mounting difficulties of mismatches, on which each poet (and each theorist) draws at different points the boundary of what is acceptable. Reuven Tsur's revised and expanded edition (original publication, Peter Lang, 1986) is essential reading for all scholars and students involved in versification and Cognitive Poetics.
1. Perception-Oriented Theory of Metre -- 2. Cognitive Assumptions : Simplicity and Multilevel Information Processing -- 3. The Empirical Rationale -- 4. Caesura -- 5. Consecutive Stresses -- 6. Stress Maximum in Weak Position -- 7. Enjambment -- 8. Disyllabic Occupancy of Metrical Position as a Perceptual Problem -- 9. Timing, Structure, Musical Key -- 10. Excursus on Hungarian Poetry and Poetry Recital -- 11. Phonetic Cues and Dramatic Function -- 12. Stress Maximum in the Fifth Position -- 13. The Structure and Delivery Style of Milton's Verse An Electronic Exercise in Vocal Performance -- 14. Metricalness and Rhythmicalness What Our Ear Tells Our Mind.
Includes bibliographical references and index.
PDF (JSTOR, viewed Nov. 7, 2022).
JSTOR
Keywords: Poetics; Versification; Oral interpretation of poetry; Poétique.; Versification; Poésie -- Lecture publique; Oral interpretation of poetry; Poetics; Versification